Exorbitant privilege? Quantitative easing and the bond market subsidy of prospective fallen angels - Viral V. Acharya; Ryan Banerjee; Matteo Crosignani; Tim Eisert; Renée Spigt (Federal Reserve Bank of New York, 2022)
We document capital misallocation in the U.S. investment-grade (IG) corporate bond market, driven by quantitative easing (QE). Prospective fallen angels - risky firms just above the IG rating cutoff-enjoyed subsidized bond financing since 2009, especially when the scale of QE purchases peaked and from IG-focused investors that held more securities purchased in QE programs. The benefitting firms used this privilege to fund risky acquisitions and increase market share, exploiting the sluggish adjustment of credit ratings in downgrading after M&A and adversely affecting competitors' employment and investment. Eventually, these firms suffered more severe downgrades at the onset of the pandemic.
Keywords: E31; E44; G21; 330; corporate bond market; investment-grade bonds; large-scale asset purchases (LSAP); credit ratings; credit ratings inflation